2001
DOI: 10.1080/01421590120075715
|View full text |Cite
|
Sign up to set email alerts
|

Students' perceptions on skills training in simulation

Abstract: The University of Pretoria implemented a problem-oriented undergraduate medical curriculum that emphasizes experiential learning and the mastering of practical skills. Students' experiences with acquiring practical skills in a skills laboratory and the impact that acquiring these skills has on their clinical practice were explored and described. A qualitative, investigative, descriptive and contextual design was used. Data were collected at focus-group discussions and analysed using Tesch's methodology. A lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In addition to the traditional lecture, seminar, and tutorial method of teaching, video clips that showed students how to cope successfully and unsuccessfully with a range of difficult situations were developed. The present study builds upon a growing literature that suggests that students can learn by watching appropriate video taped sessions (Alinier et al, 2004;Cioffi, 2001;Chau et al, 2001;Treadwell and Grobler, 2001;Cleave-Hogg and Morgan, 2002). Self-efficacy was used as the variable to assess the effectiveness of courses/modules designed to raise performance in specific skills as previous research has verified that it is predictive of performance (Bandura, 1997;Stajkovic and Luthans, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the traditional lecture, seminar, and tutorial method of teaching, video clips that showed students how to cope successfully and unsuccessfully with a range of difficult situations were developed. The present study builds upon a growing literature that suggests that students can learn by watching appropriate video taped sessions (Alinier et al, 2004;Cioffi, 2001;Chau et al, 2001;Treadwell and Grobler, 2001;Cleave-Hogg and Morgan, 2002). Self-efficacy was used as the variable to assess the effectiveness of courses/modules designed to raise performance in specific skills as previous research has verified that it is predictive of performance (Bandura, 1997;Stajkovic and Luthans, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has used simulation as part of patient health care with varying degrees of success (Alinier et al, 2004;Cioffi, 2001;CleaveHogg and Morgan, 2002;Treadwell and Grobler, 2001). Indeed, Chau et al (2001) conducted an experiment that involved 83 students completing pre-and post-tests that assessed critical thinking and knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Research on modeling behaviors by faculty has been conducted in medical schools (Treadwell & Grobler, 2001) and nursing programs (Knox & Morgan 1985;Lovric et al, 2014) for years. Lovric et al (2014) found that first-year nursing students had significantly higher expectations of their clinical faculty, particularly in terms of teaching ability, while second-year students had significantly lower expectations, mainly for the personality styles of clinical faculty.…”
mentioning
confidence: 99%